PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE-REHEARSAL PAIRS DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PATAMUAN KABUPATEN PADANG PARIAMAN - Yeni, Popy Asri; Rahmi, Rahmi; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
The background of this research was studentsâ ability in sharing information, not only theory but also less of discussion the exercise with other student optimal and the lack of the studentsâ understanding of mathematical concept. The research aimed to determine studentsâ understanding of mathematical concept by applying strategy of active learning type Practice-Rehearsal Pairs with quizzes better than the studentsâ understanding of mathematical concept with conventional learning grade VIII SMPN 1 Patamuan Padang Pariaman regency and to analysis the effectiveness of strategy of active learning type Practice-Rehearsal Pairs with quizzes in learning mathematics. It was an experimental research with the design random on the subject. Instrument used was an essay test and questionnaire which already validated. Hypothesis testing which was used by one side of t test with program MINITAB 14, in which p-value 0,003 smaller than Î± 0,05 it mean that the alternative hypothesis was accepted. It can be concluded that the studentsâ understanding of mathematical concept with strategy of active learning types Practice-Rehearsal Pairs with quizzes better than by applying conventional learning.